Exact solutions for coupled KdV equation and KdV equations - Inan, Ibrahim E. (Elsevier Science Bv, 2007)
We implemented a generalized tanh function method for approximating the solution of the coupled KdV equation and KdV equation. By using this scheme, we found some exact solutions of the coupled KdV equation. For the further investigation of the method, some exact solutions of the KdV equations have also obtained. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: KdV equation; coupled KdV equations; generalized tanh function method; traveling wave solutions